Evaluation of safety standards accomplishment in educational hospitals of Neyshabur University of Medical Sciences-Iran - Kavosi, Ali (MethodsX, 2019)
Patient’s safety and staff in hospital is one issue that has always been considered as an important principle by experts in health systems. Therefore, for increase safety, standards and safety regulations must be considered. This study aims to evaluation of safety standards accomplishment in educational hospitals of Neyshabur University of medical Sciences. This cross-sectional descriptive study, safety standard status of all wards including 17 various wards from 22 Bahman hospital and 14 various wards from hakim Hospital in Neyshabur city (2016) was investigated. Data were collected using a questionnaire safety standard status hospitals (264 questions). Also data analyzed by SPSS16 software, using descriptive (Mean ± SD) and inferential statistics (T-Test). The results revealed that Safety standard status in 22bahman and hakim hospital were weak (2.42 ± 0.14) and moderate (3.04 ± 0.18) respectively. Also result showed in Hakim hospital, the highest and lowest safety standard status in Internal and Administrative-financial unit was (3.42 ± 0.19) (1.36 ± 0.58) respectively. In addition in hakim hospital, the highest and lowest safety standard status in operation room and administrative-financial unit (3.53 ± 0.28), 1.36 ± 0.58) respectively. According to the result, the safety condition in hospitals of Neyshabur city is moderate and poor status. However, imperfect implementation of safety protocols can endanger safety conditions in hospital. Therefore, it is necessary to take the required correcting measures to ensure full safety in hospitals. • Safety is defined by development of systems for preventing incidents, injuries, and other unpleasant events in organizations. • This article showed the safety status is not appropriate in most units of hospitals, which can lead to dangers for patients and personnel. • It is suggested for future studies to compare the safety status of different provinces.